Anammox granule as new inoculum for start-up of anaerobic sulfide oxidation (ASO) process and its reverse start-up. (February 2019) - Shi, Zhi-Jian; Xu, Lian-Zeng-Ji; Wu, Dan; Cheng, Ya-Fei; Zhang, Fu-Yue; Liao, Si-Mo; Zhang, Zheng-Zhe; He, Miao-Miao; Jin, Ren-Cun
Abstract: The feasibility of implementing anaerobic ammonium oxidation (anammox) granules to start up high-loading anaerobic sulfide oxidation (ASO) in an upflow anaerobic sludge bed (UASB) reactor was investigated. An innovation method of the reverse start-up of anammox was also validated. Firstly, the reactor was operated to treat sulfide-rich wastewaters into which nitrite was introduced as an electron acceptor. An high-rate performance with sulfide and nitrate removal rates of 105.5 ± 0.11 kg S m −3 d −1 and 28.45 ± 3.40 kg N m −3 d −1, respectively, was accomplished. Sulfurovum were enriched with the increase of the substrate load and then conquered Candidatus Kuenenia to be the predominant bacteria. Excitation-emission matrix (EEM) spectroscopy showed that the intensities of fluorescence decreased and protein-like substrates were the main components associated with the process of start-up. FT-IR analysis found that the main functional groups indicator were O-H groups. Secondly, the reverse start-up of anammox (achieving 90% TN removal) was achieved immediately when the substrate changed. 16S rRNA analysis indicated the successfully enrichment of anammox bacteria ( Candidatus Kuenenia ). These results suggest that anammox granules can act as inoculum of high-loading ASO process and the reverse start-up provides a new perspective for the fast initiation of anammox process. Graphical abstract: Highlights: High-loading ASO process was started up by inoculation of anammox sludge. Microbial community dynamics over different operational periods were revealed. The reverse start-up of anammox process was quickly achieved. EEM and FT-IR spectroscopy were employed to characterize changes in EPS.